Analisis Demografis Pembeli Ikan di Pasar Rakyat Batu Cermin, Labuan Bajo - Kristoforus Toni Harjo; Luh G.E.A. Saputri; I Wayan Pio Pratama; Eka Sudarsana; Angling G.C Widiyanto (Pusat Penelitian dan Pengabdian Politeknik eLBajo Commodus, 2024)
Demographic analysis of fish buyers at Batu Cermin Traditional Market, Batu Cermin Village, West Manggarai, East Nusa Tenggara, with the aim of understanding consumption patterns and community preferences. The study used a quantitative descriptive method based on primary data obtained through questionnaires from 300 respondents. The variables analyzed included gender, age, occupation, income, and type of fish purchased. The results showed that the majority of fish buyers were male (193 people), with the 17–24 age group as the dominant consumers (194 people). Based on occupation, students (157 people) were the largest group of buyers, followed by entrepreneurs (104 people). Most buyers came from low-income groups (Rp 0–1,000,000 per month, 195 people). The types of fish most commonly purchased were tembang fish (142.5 kg), layang (137.2 kg), and tuna (123.4 kg), which are popular due to their affordable prices and availability. This study shows that the Batu Cermin traditional market plays a strategic role as a source of affordable food for the community, especially for young and low-income groups. These findings can form the basis for developing policies that support local economic sustainability, increased food access, and better market management keywords: demographic analysis, fish buyer, local market, Batu Cermin , Labuan Bajo.